The Effect of Intellectual Capital and Islamic Corporate Governance on Islamic Social Reporting Disclosure with Financial Performance Mediation - Ichsan Setiyo Budi; Rahmawati Prof Rahmawati Prof (Bina Nusantara University, 2019)
This research aimed to examine the indirect effect of Islamic Corporate Governance (ICG) disclosure and Intellectual Capital (IC) on Islamic Social Reporting (ISR) disclosure with financial performance as a mediating variable in Islamic Banking in Indonesia. It used secondary data with annual report data sources and financial statements on Islamic banking in Indonesia. They were testing this research using regression analysis with data for the annual reporting period of 2011 through 2014. The result finds that ROE mediates the effect of ICG on ISR disclosure. This shows that good management of Islamic banks will produce high financial performance so that they are able to carry out their social roles well too. The contribution of this research is to develop a new model of the role of financial performance mediating the effect of ICG disclosure on ISR so that it is beneficial for the development of science.